The Physical and Chemical Properties of Natural Drinking Water in Phonexay District, Lao PDR: https://doi.org/10.69692/sujournal2024.10.1.140-147 - BOUASAVANH, Souvanh; KEOHAVONG , Bounmy; KANDEE, Thanousinh (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This study aims to determine the physical, chemical and biological properties and capacity of the commercial purifier (TerraClear ceramic water purifier) of natural drinking water. The present study was conducted in three villages of Phonexay district, Luang Prabang province, Lao PDR where the purifiers were provided for the target households. The surface water was collected before and after purifications. The collected samples were sent to the laboratory of the Water Supply Company for the analysis of physical, chemical and biological compositions. The result showed that: The compositions of physical. pH, Conductivity (uS/cm), Turbidity (NTU), Color (TCU) before purifications were 7.56, 261.00, 6.38, 5.66 The values after purifications were 7.50, 239.00, 0.45, 0.66 The compositions of chemical. Fluoride (mg/L), Nitrate (mg/L), Nitrite (mg/L), Total Hardness (CaCo3: mg/L), Arsenic (mg/L), Iron (mg/L), Manganese (mg/L) before purifications were 0.15, 1.13, 0.01, 132.00, 0.00, 0.05, 0.01 The values after purifications were 0.02, 0.36, 0.002, 18.00, 0.00, 0.02, 0.01 The compositions of biological. Coliform bacteria (100ml), E-Coli (100ml) before purifications were 53.33, 2.33 The values after purifications were 0.00, 0.00, respectively. The natural surface water in the northern province of Lao PDR is not seriously harmful in some areas as well as in the remote areas in terms of biological, physical and chemical contaminations. Moreover, this study confirmed that using the TerraClear ceramic water purifier was safe for drinking water for people and its exceeded chemical compositions which could be harmful to human health were also purified. Further research is recommended to classify more details and varies of other related biological and chemical contaminations.